Peningkatan Mutu Pembelajaran Kurikulum Paradigma Baru melalui Lesson Study di SMPN 1 Lengkong - Achmad Rijanto; Suesthi Rahayuningsih (CV. Multi Kreasi Media, 2022)
This community service activity has been carried out at SMP Negeri 1 Lengkong, Nganjuk Regency. The problem faced by service partners is the lack of quality in the learning process in implementing the new paradigm curriculum, especially the lack of teachers who make lesson plans and the lack of teacher innovation in learning. The purpose of this service is to improve the quality of learning in implementing the new paradigm curriculum, through lesson study in partner schools, especially improving the quality of teachers in making lesson plans and improving the quality of teachers innovating in the implementation of learning. The service method used is to provide training in the form of technical guidance to teachers at partner schools related to the new paradigm curriculum and lesson study. The results achieved from this service are improvements in the quality of teacher learning, especially for grade 7 teachers who apply the new paradigm curriculum by 85% .